Circulating tumor cells (CTCs) in breast cancer: a diagnostic tool for prognosis and molecular analysis - Dong, Xiaoshen; Alpaugh, Katherine R.; Cristofanilli, Massimo (Chinese Journal of Cancer Research; Vol 24, No 4 (December 07, 2012): Chinese Journal of Cancer Research, 2012)
Metastatic breast cancer (MBC) is characterized by a combination of tumor growth, proliferation and metastatic progression and is typically managed with palliative intent. The benefit of standard systemic therapies is relatively limited and the disease is considered incurable suggesting the need to investigate the biological drivers of the various phases of the metastatic process in order to improve the selection of molecularly driven therapies. The detection, enumeration and molecular analysis of circulating tumor cells (CTCs) provide an intriguing opportunity to advance this knowledge. CTCs enumerated by the Food and Drugs Administration-cleared CellSearch® system are an independent prognostic factor of progressionfree survival (PFS) and overall survival (OS) in MBC patients. Several published papers demonstrated the poor prognosis for MBC patients that presented basal CTC count ≥5 in 7.5 mL of blood. Therefore, the enumeration of CTCs during treatment for MBC provides a tool with the ability to predict progression of disease earlier than standard timing of anatomical assessment using conventional radiological tests. During the metastatic process cancer cells exhibit morphological and phenotypic plasticity undergoing epithelialmesenchymal transition (EMT). This important phenomenon is associated with down regulation of epithelial marker (e.g., EpCAM) with potential limitations in the applicability of current CTCs enrichment methods. Such observations translated in a number of investigations aimed at improving our capabilities to enumerate and perform molecular characterization of CTCs. Theoretically, the phenotypic analysis of CTCs can represent a “liquid” biopsy of breast tumor that is able to identify a new potential target against the metastatic disease and advanced the development and monitoring of personalized therapies.